DEVELOPING THE COMPETENCE OF PUBLIC CIVIL SERVANTS: REQUIREMENTS AND OPPORTUNITIES OF THE NEW ERA (Scientific electronic journal "Labor Economics and Human Capital", 2024)
In this article, the issue of capacity development of state civil servants in the era of globalization was studied. The advanced methods of the developed countries were comparatively studied, and the new requirements for civil servants in Uzbekistan were analyzed. On the basis of a comparative analysis of theoretical perspectives, the theories of human capital development, continuous education, institutional reforms and digital transformation were considered. Successes and existing problems in the development of public service were identified through practical analysis.
Keywords: State civil servants, personnel capacity, professional development, improvement of human resources, digital technologies.